A Study on the Relevance of Indonesian Civil Law in Resolving EPC FIDIC Silver Book Contract Disputes Through Bani Arbitration - Bona Ary Napitupulu; Sarwono Hardjomuljadi; Sami’an Sami’an; Ganis Vitayanti Noor (International Journal Labs, 2026)
EPC (Engineering, Procurement, and Construction) contracts are increasingly used in large infrastructure projects in Indonesia due to their efficiency and clear division of responsibilities (Federation Internationale des Ingenieurs-Conseils [FIDIC], 2017). However, this contract is rooted in a Common Law system that is different from Indonesia's national legal system which adheres to Civil Law (Subekti, 2019; Satrio, 2021). This study aims to analyze the extent to which the Indonesian Civil Law system is able to maintain its legal sovereignty in the implementation of FIDIC Silver Book-based EPC contracts, as well as identify legal challenges that arise due to differences in legal principles. The method used is a normative juridical approach combined with conceptual and comparative analysis of the provisions of the Civil Code (1847), Law Number 2 of 2017 concerning Construction Services (Law of the Republic of Indonesia, 2017), and risk allocation and dispute resolution clauses in the FIDIC Conditions of Contract (FIDIC, 2017). The results of the study show that there are fundamental differences in the principle of risk sharing and dispute resolution mechanisms between the Common Law and Civil Law systems. Several clauses in FIDIC require harmonization to be in line with the principles of justice, legal certainty, and proportionality that apply in national law (Hidayat, 2021; Osei, 2022). This research contributes to strengthening academic and practical understanding of the harmonization between international contracts and national law. These findings are expected to be a conceptual basis for the development of adaptive construction legal norms while maintaining Indonesia's legal sovereignty (Lubis, 2020; Klee, 2021).